Microcornea, iris and choroidal coloboma, and global developmental delay caused by TENM3 pathogenic variants in a Chinese patient. Issue 6 (9th April 2022) - Zhou, Youfeng; Xu, Ke; Gu, Weiyue; Huang, Yan
Abstract: Background: Biallelic TENM3 pathogenic variants cause isolated or syndromic microphthalmia. Syndromic microphthalmia 15 (MCOPS15) is characterized by microphthalmia, coloboma, and developmental delay. Currently, only four cases of MCOPS15 have been reported and the clinical features varied among the patients indicating potential broad phenotypic spectrum. Methods: The present case was a 6‐month‐old male at diagnosis. The patient exhibited long philtrum, large ears, bilateral ptosis, and nystagmus. Ophthalmic tests showed that he had microcornea, iris and choroidal coloboma. The patient presented with global developmental delay (GDD). Trio‐whole exome sequencing and genome copy number sequencing were conducted to explore the disease‐causing mutations. Results: Exome sequencing and genome copy number sequencing showed the presence of L1471F and E661G compound mutations in TENM3, which were inherited from the mother and father, respectively. Sanger sequencing was conducted to verify association of the mutations with the disease in the present family. Conclusion: Two TENM3 variants were identified in a patient with Syndromic microphthalmia 15 in the present study. However, further studies should be conducted to explore the pathogenicity of the variants. Abstract : To date, only four cases of MCOPS15 were reported and the clinical features of the patients were variable, which indicate potential broad phenotypic spectrum. In this study, using trio‐whole exome sequencing, we identified biallelic variants (L1471F and E661G) of TENM3, in a 6 months Chinese boy. Our findings expand the mutational spectrum of the TENM3 gene, which might help increases understanding of the heterogeneity of clinical manifestations of diseases.